CFRP strengthening of fatigue cracks at U-rib to diaphragm welds in orthotropic steel bridge decks: Experimental study, optimization, and decision-making. (September 2022) - Jiang, Fei; Ding, Youliang; Song, Yongsheng; Geng, Fangfang; Wang, Zhiwen
Abstract: This paper investigated fatigue strengthening of U-rib to diaphragm welds in orthotropic steel bridge decks (OSDs) using the carbon fiber-reinforced polymer (CFRP). Fatigue testing and CFRP strengthening were performed on a full-scale OSD specimen with several U-rib to diaphragm welds. A strengthening configuration was proposed during the experiment. The testing results show that the attachment of CFRP plates on the cracked U-rib wall performed well in reducing both the local fatigue stresses and the average crack growth rate. Then, a multi-objective optimization and decision-making framework was proposed to realize the optimum design of the strengthening configuration. Considered the critical factors to the strengthening efficiency and cost, the material elastic moduli, CFRP size, and strengthening timing were chosen as design variables while maximizing the strengthened fatigue performance and minimizing the total cost were together regarded as the optimization targets. Considering the uncertainty of macrocrack propagation, Monte Carlo Simulation was used to predict the lifecycle fatigue life distribution. Then, a probabilistic assessment criterion for the strengthed fatigue performance was derived by theoretical derivation. Repeated numerical simulations were conducted to obtain the strengthened stress intensity factors using a multi-scale OSD model. Based on these simulated data, a surrogate model of the optimization objective was developed by Response Surface Methodology, which successfully considered the interaction effects between multiple design variables. Finally, the optimum CFRP strengthening configurations were derived by genetic algorithm and multi-attribute decision-making. This study is convinced to not only advance our understanding of CFRP strengthening of U-rib to diaphragm welded joints but also facilitate the optimum application of CFRP material in maintaining deteriorating steel structures.